Sedentary behaviour among older adults residing in flat and hilly neighbourhoods and its association with frailty and chronic disease status - Nestor Asiamah; Simon Mawulorm Agyemang; Edgar Ramos Vieira; Hafiz T. A. Khan; Janvier Gasana (BMC, 2023)
Abstract Background Living in hilly neighbourhoods can be associated with sedentary behaviour, but no study has compared sedentary behaviour and its associations with frailty, chronic diseases, and poor health between flat and hilly neighbourhoods among older adults. This study, therefore, compared older adults' sedentary behaviour and its association with frailty, poor health, and chronic disease status between low and hilly neighbourhoods. Methods This study utilised a STROBE-compliant cross-sectional design with sensitivity analyses and a common methods bias assessment. The participants were 1,209 people aged 50+ years who resided in flat (Ablekuma North, n = 704) and hilly (Kwahu East, n = 505) neighbourhoods in Ghana. The data were analysed with the independent samples t-test and hierarchical linear regression. Results Older adults in the hilly neighbourhood were more sedentary than those in the flat neighbourhood. The association between sedentary behaviour and chronic disease status was significant in both neighbourhoods, but this relationship was stronger in the hilly neighbourhood. Older adults in the flat neighbourhood reported lower sedentary behaviour at higher frailty (β = -0.18; t = -3.2, p < 0.001), but those in the hilly neighbourhood reported higher sedentary behaviour at higher frailty (β = 0.16; t = 3.54, p < 0.001). Conclusions Older adults living in the hilly neighbourhood reported higher sedentary behaviour. In the hilly neighbourhood, sedentary behaviour was more strongly associated with frailty and chronic disease status. Older adults in hilly neighbourhoods may need extra support to avoid sedentary behaviour.